Answer:
See below.
Explanation:
(a) Because the solution led to a square root of a negative number:
x^2 -10x+40=0
x^2 - 10x = -40 Completing the square:
(x - 5)^2 - 25 = -40
(x - 5)^2 = -15
x = 5 +/-√(-15)
There is no real square root of -15.
(b) A solution was found by introducing the operator i which stands for the square root of -1.
So the solution is
= 5 +/- √(15) i.
These are called complex roots.
(c) Substituting in the original equation:
x^2 - 10 + 40:
((5 + √(-15)i)^2 - 10(5 + √(-15)i) + 40
= 25 + 10√(-15)i - 15 - 50 - 10√(-15)i + 40
= 25 - 15 - 50 + 40
= 0. So this checks out.
Now substitute 5 - √(-15)i
= 25 - 10√(-15)i - 15 - 50 + 10√(-15)i + 40
= 25 - 15 - 50 + 40
= 0. This checks out also.